HOW INDONESIAN TOURIST MOTIVATION CAN ENCOURAGE THE DESIRE HAVE BEEN TO BANGKOK, THAILAND - Ningrum, Lestari; Dito Dwiseptian, Anggi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2019)
Compared to other ASEAN countries, Thailand excels in terms of tourism growth in 2016. The period of January to October 2016, 27.076.308 Indonesian tourists visited Thailand, while Thailand’s tourists visit to Indonesia only 9.403.614. Why it happened? Whereas Indonesia including the 6 most beautiful country sites version Rough Guides, beating some countries such as the UK, Switzerland and Finland, and was chosen because of the cluster of gathering, cultural diversity, volcanoes, and even Indonesia became the only Asian country in the top 10 Tourism is worldwide. Tourism is currently experiencing a shift in the role. For many cities in Indonesia, travel has become a primary need. Motivational factors are also related to visitor’s satisfaction because different destination may have different factors that attract visitor to the place. The research method used in this study is descriptive with quantitative approach. The research instrument is questionnaire with 5-point likert scale, distributed either directly on the site with 397 respondents who have ever travelled to the locations under study. The aim of research how Indonesian tourist motivation can encourage the desire been to Bangkok Thailand The results showed that the motivation of the traveller physical, the strongest impulse to travel to Bangkok is with the aim to refreshing.Key works: Tourism, travel motivational